SYNAPTONEMAL COMPLEX-ANALYSIS OF THE SEX BIVALENT IN GOATS - Amaral, MEJ; Jorge, W. (Elsevier B.V., 1994)
Synaptonemal complex (SC) analysis of XY pairing in the goat (Capra hircus; 2n = 60) was investigated by electron microscopy for the first time in this species. Synapsis of the X and Y chromosomes begins during the mid-late zygotene stage as the autosomes complete their pairing. Only a small portion of the total length of the Y is paired with the X chromosome at this time. By the early pachytene, almost 90% of the Y is paired with the X. All the observed stages of the sex bivalent pairing showed the structural difference between the differential and pairing regions. In the pairing region, a synaptonemal complex is formed, while in the differential region the chromosome axes remain free.
Keywords: SYNAPTONEMAL COMPLEX; MEIOSIS; PACHYTENE; XY BIVALENT; GOAT